Premoženjska razmerja med zakonci v mednarodnem zasebnem pravu - Rudolf, Claudia (Podjetje in delo, 2018)
Regulation 2016/1103 shall apply to matrimonial property regimes and comprises harmonised conflict-of-law rules, rules on jurisdiction, recognition, enforceability and enforcement of decisions, authentic instruments and court settlements. The spouses can choose the law applicable to their matrimonial property regime among the laws with which they have close links because of habitual residence or their nationality. In the absence of a choice of law, the applicable law is determined on the basis of a scale of connecting factors.
Keywords: mednarodno zasebno pravo; premoženjska razmerja; Uredba Sveta (EU) 2016/1103; zakonci